Apple grower pollination practices and perceptions of alternative pollinators in New York and Pennsylvania. Issue 1 (25th February 2020) - Park, Mia G.; Joshi, Neelendra K.; Rajotte, Edwin G.; Biddinger, David J.; Losey, John E.; Danforth, Bryan N.
Abstract: Pollinator declines coupled with increasing demand for insect pollinated crops have the potential to cause future pollinator shortages for our most nutritious and valuable crops. Ensuring adequate crop pollination may necessitate a shift in pollination management, from one that primarily relies on the managed European honeybee ( Apis mellifera L.) to one that integrates alternative pollinators. While a growing body of scientific evidence supports significant contributions made by naturally occurring, native bees for crop pollination, translating research to practice requires buy-in from growers. The intention of agricultural extension is to address grower needs and concerns; however, few studies have assessed grower knowledge, perceptions and attitudes about native pollinators. Here we present findings from questionnaire-based surveys of over 600 apple growers in New York State and Pennsylvania, coupled with ecological data from bee surveys. This hybrid sociological and biological survey allows us to compare grower knowledge and perceptions to an actual pollinator census. While up to 93% of respondents highly valued importance of native bees, 20% growers did not know how much native bees actually contribute to their orchard pollination. Despite the uncertainty, a majority of growers were open to relying on native bees (up to 60% in NY and 67% in PA) and to making low-cost changes to their farm's management that would benefit native pollinators (up to 68 in NY and 85% in PA). Growers consistently underestimated bee diversity, but their estimates corresponded to major bee groups identifiable by lay persons, indicating accurate local knowledge about native bees. Grower reliance on honeybees increased with farm size; because native bee abundance did not measurably decrease with farm size, renting honeybees may be motivated by risk avoidance rather than grower perception of lower native bee activity. Demonstrated effectiveness of native pollinators and clear guidelines for their management were the most important factors influencing grower decision to actively manage orchards for native bees. Our results highlight a pressing need for an active and research-based extension program to support diversification of pollination strategies in the region.